THE EFFECTS OF LABOUR COSTS REDUCTION ON FOREIGN INVESTMENT IN ROMANIA - TRANDAFIR, Adina (Annals of Spiru Haret University. Economic Series, 2019)
This article addresses the issue of changes in tax legislation in our country over the last 20 months, in view of the effect they have on the level of foreign investment. The article presents, besides the actual legislative changes and the evolution registered in this period by foreign investments, also the fiscal pressure in the field of contributions, VAT and corporate income tax. The paper presents an econometric analysis that seeks to highlight the impact of the fiscal pressure of the above mentioned taxes on the FDI level recorded in Romania between January 2017 and August 2018.